Strategi Mengelola Pendapatan Ojek Online Terhadap Kesejahteraan Keluarga - Rustomo Rustomo; Partimah Partimah; Jhosua Parningotan Pandiangan (ITB AAS Indonesia Surakarta, 2024)
Indonesia is a developing country that has very high growth in productive forces. The aim of this research is to discuss the concept of the presence of job providers as a hope for productive people. Gojek is one of the providers providing employment opportunities with various conveniences. Productive people can earn wages/income by working as application-based Gojek drivers. By managing income effectively and efficiently, needs will met as a concept for the welfare of the family. Using quantitative correlational research methods with questionnaire-based data collection techniques with primary data results. Using a linkage scale of 1-5 distributed to 33 respondents. Nonprobability sampling technique incidental sampling is a technique for determining samples based on chance, anyone who accidentally met by the researcher is declared to representative as a respondent. The conclusion of the data processing results is that all statements declared valid and reliable. The data declared normal and does not occur heteroscedasticity, has a strong positive relationship with the influence of two significant variables on the decision to accept the alternative hypothesis and reject the initial hypothesis. It recommended that Gojek drivers must work hard in order to provide for the welfare of their families